Design and Development of Interactive Digital Comic Media to Foster Historical Consciousness and Islamic Thought: a Case Study at MTsN 2 Sidenreng Rappang, Indonesia - Kurniawan, MN. Rahmat; Jamilah, Sitti; Saleh, Muhammad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to develop an interactive digital comic-based learning medium to foster students’ historical consciousness and Islamic thought while improving their understanding of Islamic history at Madrasah Tsanawiyah Negeri 2 Sidenreng Rappang. Using the Research and Development (R&D) method with the ADDIE model—analysis, design, development, implementation, and evaluation—this research produced a digital comic entitled The Siege of Jerusalem by Umar bin Khattab as a learning medium for the subject of Islamic Cultural History (SKI). The digital comic does not merely visualize historical events but is deliberately designed to build Islamic historical awareness by presenting history as ‘ibrahand to instill an Islamic worldview on justice, tolerance, and leadership through the character of Umar bin Khattab. Data were collected through observation, interviews, questionnaires, and tests. The results showed that traditional learning media remained dominant and less engaging, leading to low motivation and limited comprehension. The developed digital comic improved students’ learning outcomes by 14 points and increased motivation, accompanied by higher levels of historical reflection and the ability to connect the conquest of Jerusalem to the values of justice, tolerance, and mercy within Islamic thought. Qualitative data from students and teachers also indicated deeper historical awareness and internalization of Islamic ethical values. Thus, Islamic-values-based digital comic media effectively enhances cognitive understanding while fostering Islamic historical consciousness, moral reflection, and students’ interest in learning Islamic history.